Potential of Bacillus subtilis inoculation in Biorichar™ amended soil for suppression of Fusarium wilt of banana (Musa acuminata cv. Berangan) under water stress condition - Mohd Din, Siti Norliza; Sakimin, Siti Zaharah; Sijam, Kamaruzzaman; Ramlan, Mohd Fauzi; Hossein, Ali Baghdadi; Zakaria, Md Aiman Takrim (Farm to Fork Foundation, 2018)
The present research was conducted to evaluate the ability of Bacillus subtilis to supress Fusarium wilt disease of banana in Biorichar™ amended soil under different soil moisture regimes. Banana plants were inoculated with different volumes of Bacillus subtilis (0, 20, 40 and 60 mL) given at concentration 108 CFU mLˉ¹ and subjected to three water stress levels based on field capacity (FC) viz. well watered (100% FC), mild stress (75% FC), and severe stress (50% FC). Banana plantlets were inoculated with Fusarium oxysporum one week after Bacillus subtilis were applied. The results showed that, minimum percentage of disease incidence in banana plants was recorded at high Bacillus subtilis rate (40 mL and 60 mL) at 50% FC. However, at 75% FC and 100% FC conditions, disease incidence increased from 35.28% to 45.09% following the time. Proline content showed 0.33% high under 75% FC compared to 50% FC at 45 DAT and similar trend was observed at 90 DAT. Malondialdehyde (MDA) content in banana plants was high in control treatment than those inoculated with Bacillus subtilis. 100% FC condition gave significantly higher net photosynthesis (14.95%), stomatal conductance (60.47%), transpirations rate (54.58%) and vapor pressure deficit (14.14%) compared to 50% FC at 45 DAT. However, values of net photosynthesis at 90 DAT were 30.07% and 20.79% lower at 50% FC and 100% FC, respectively in comparison to the values recorded at 45 DAT as pathological process progressed. Inoculation of Bacillus subtilis @ 60 mL increased photosynthesis rate by 9.07% as compared to non-inoculated plantlets at 100% FC at 45 DAT. However, no significant difference observed when the plants were inoculated by Bacillus subtilis @ 40 mL and @ 60 mL under 75% FC condition. Therefore, inoculation of Bacillus subtilis @ 60 mL could be a promising biological control agent that can trigger resistance against Fusarium wilt in susceptible Berangan banana under water stress condition.